How Turbulence Brings Benefit: The Influence of Dynamic Team Environment on Entrepreneurial Team Innovation - Deng, Xiao; Wang, Ying; Sun, Xiuli (Frontiers in Psychology, 2020)
From the perspective of entrepreneurial team processes, this study examines the effect of dynamic team environment on entrepreneurial team innovation. Through applying the uncertainty reduction theory and group process theory, this study proposes the influence mechanism and boundary condition of the relationship between dynamic team environment on entrepreneurial team innovation. By analyzing a sample of 270 entrepreneurial teams in China, this study found that dynamic team environment could evoke entrepreneurial team innovation via triggering team members’ agreement seeking behavior and then promoting team knowledge integration. In addition, team centralization of decision making can weaken the relationship between agreement seeking behavior and team knowledge integration. Our findings contribute to a better understanding of entrepreneurial teams’ reactions to dynamic environment and the multistep mechanism that transfers the impact of dynamic team environment to entrepreneurial team innovation through team members’ reactions and team interactions.